Green Curmin Reduces Pro-inflammatory Cytokines and Fibroblast-Associated Colon Cancer Migration - Nasapon Povichit; Tharathip Muangthong; Parichaya Aimvijarn; Prasit Suwannalert (Tabriz University of Medical Sciences, 2021)
Background: Green Curmin is a soluble curcumin extract product made in Thailand that has been reported to reduce gastric inflammation. Inflammatory cytokines including IL-1α, IL-6,and TNF-β play a crucial role in cancer cell migration, which is a major development towards poor prognosis. The aim of this study is to investigate the effects of Green Curmin on colon cancer cell growth and migration, which involve pro-inflammatory cytokines. Methods: Curcuma longa L. were extracted and named Green Curmin. The cytotoxicity of theGreen Curmin-treated HCT116-colon cancer cells was obtained by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and flow cytometry. The effect of the extract on cancer migration was investigated with a wound-healing assay. In addition, fibroblast-associated cancer migration was confirmed by using the Transwell migration assay. Proinflammatory cytokines were also determined. Results: Green Curmin had cytotoxicity in the induced-cancer cell apoptosis at concentrationsof 1 and 5 mg/ml. However, reduced colon cancer migration and fibroblast associated-cancermigration was found at concentrations of 0.05 and 0.1 mg/ml (non-toxicity dose), respectively. They also suppressed pro-inflammatory cytokines expression including IL-1α, IL-6, and TNF-βin colon cancer cells and IL-6 in fibroblast cells. Conclusion: Green Curmin has the potential to suppress pro-inflammatory cytokines and reduce fibroblast associated-cancer migration.